CONSTRUCTION FIRM READINESS TOWARDS IMPLEMENTING INTEGRATED PROJECT DELIVERY (IPD) - Mohd Nawi, Mohd Nasrun; Osman, Wan Nadzri; Mohd Shafiei, Mohd Wira; Ibrahim, Fazdliel Aswad; A. M., Mustafa Al Bakri (International Journal of Supply Chain Management, 2017)
The Malaysian government has taken the initiative of implementing Industrialised Building System (IBS) in which components are manufactured in mass production under a controlled environment (on or off site), transported, positioned and assembled into a structure with minimal additional site works. It is hope that IBS can improve the performance of construction industry. However, one of the main barriers in Malaysian IBS implementation is lack of integration among stakeholder involved during the project delivery stage. In order to overcome this barrier, a new collaborative procurement or project delivery namely as Integrated Project Delivery (IPD) which is using a multi-party contract (more than two parties selected) has been introduced. Integrated Project Delivery (IPD) is defined as a project delivery approach that integrates people, systems, business structures and practices into a process that collaboratively harnesses the talents and insights of all project participants to optimise the results, increase value to the owner, reduce waste, and maximize efficiency through all phases of design, fabrication and construction. Although, many researchers have argue the importance of IPD in project delivery process, but the readiness of construction industries must be established. This research has used a quantitative research process that involved a few phases including literature review stage, data collection stage, framework development stage, validation and recommendation stage. This research is to obtain data based on multidisciplinary IBS stakeholders perspectives, respondent include project managers, resident engineers, architects and contractors are among the potential candidates. Respondents that directly involved in the construction industry mentioned that their firms are willing to change and implement IPD. The firm s readiness recorded at the moderate mean value. It can be noted that each firm involved as respondents are ready to implement.